Nitric oxide inhibits prostanoid synthesis in the rat oviduct - Perez Martinez, Silvina Laura (2000)
We have studied the effect of nitric oxide (NO) on the production of arachidonic acid ([14C]-AA) metabolites in the rat oviduct. The basal synthesis of eicosanoids was measured by the conversion of ([14C]-AA) to the different radiolabeled products of cyclooxygenase (COX). The oviducts incubated for 1h with the labeled substrate of COX were able to convert 3.3 ± 0.3% of ([14C]-AA) to 6-ceto-PGF(1α), 10.7 ± 1.0% to PGF(2α), 13.5 ± 1.2% to PGE2 and 6.3 ± 0.5% to TXB2. The tissues were incubated with different doses of two NO donors: SIN-1 and Spermine NONOate. The results indicated that SIN-1 produces a significant decrease (50%; P<0.05) in all prostanoids evaluated in a dose-response fashion. The inhibitory effect was completely reversed by addition of 20 μg/ml of hemoglobin (Hb), a NO scavenger. The addition of Spermine NONOate to the incubation medium diminished significantly (65%) the synthesis of COX metabolites suggesting that NO acts by inhibiting COX activity in the rat oviduct. However, NOS inhibitors, N(G)-L-arginine-methyl-ester (L-NAME) nd N(G)-L-monomethyl-arginine (L-NMMA) had no effect on basal production of the prostanoids. These results indicate that in the rat oviduct the synthesis of COX metabolites is negatively regulated by nitric oxide. (C) 2000 Harcourt Published Ltd.